A critique and analysis of jurisprudential views on the ruling for the sales of unknown with supplement - Ã˜ÂÃ›ÂŒÃ˜Â¯Ã˜Â±Ã›ÂŒ Ã˜Â®Ã™ÂˆÃ˜Â±Ã™Â…Ã›ÂŒÃ˜Â²Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Substitute - either the sale or the price - needs to be clearly determined in terms of amount, substance or material, and any characteristics influencing the fee. And, the condition for the validity of the deal is that the two sides completely know and be aware of the contract being negotiated. Thus, if one side is mindful (informed) of the contract but the other is ignorant (uninformed), the deal is void. This is because in the case of ignorance to the object of the deal, it will be a risky one denounced by the Legislator; as we can read in the hadith: âThe Prophet has forbidden risky sales.â In the present paper, seven narratives have been reported all in all as regards the sales of unknown with supplement, insisting on the validity the sale. A number of arguments against this validity have also been mentioned. Then, the supportive and disproving views are critically reviewed. Finally, the invalidity and nullity of the sales of unknown with supplement.